Relationship Between Deltoid and Rotator Cuff Muscles During Dynamic Shoulder Abduction: A Biomechanical Study of Rotator Cuff Tear Progression. Issue 8 (July 2018) - Dyrna, Felix; Kumar, Neil S.; Obopilwe, Elifho; Scheiderer, Bastian; Comer, Brendan; Nowak, Michael; Romeo, Anthony A.; Mazzocca, Augustus D.; Beitzel, Knut
Background: Previous biomechanical studies regarding deltoid function during glenohumeral abduction have primarily used static testing protocols. Hypotheses: (1) Deltoid forces required for scapular plane abduction increase as simulated rotator cuff tears become larger, and (2) maximal abduction decreases despite increased deltoid forces. Study Design: Controlled laboratory study. Methods: Twelve fresh-frozen cadaveric shoulders with a mean age of 67 years (range, 64-74 years) were used. The supraspinatus and anterior, middle, and posterior deltoid tendons were attached to individual shoulder simulator actuators. Deltoid forces and maximum abduction were recorded for the following tear patterns: intact, isolated subscapularis (SSC), isolated supraspinatus (SSP), anterosuperior (SSP + SSC), posterosuperior (infraspinatus [ISP] + SSP), and massive (SSC + SSP + ISP). Optical triads tracked 3-dimensional motion during dynamic testing. Fluoroscopy and computed tomography were used to measure critical shoulder angle, acromial index, and superior humeral head migration with massive tears. Mean values for maximum glenohumeral abduction and deltoid forces were determined. Linear mixed-effects regression examined changes in motion and forces over time. Pearson product-moment correlation coefficients ( r ) among deltoid forces, critical shoulder angles, and acromial indices were calculated. Results: Shoulders with an intact cuff required 193.8 N (95% CI, 125.5 to 262.1) total deltoid force to achieve 79.8° (95% CI, 66.4° to 93.2°) of maximum glenohumeral abduction. Compared with native shoulders, abduction decreased after simulated SSP (–27.2%; 95% CI, –43.3% to –11.1%, P = .04), anterosuperior (–51.5%; 95% CI, –70.2% to –32.8%, P < .01), and massive (–48.4%; 95% CI, –65.2% to –31.5%, P < .01) cuff tears. Increased total deltoid forces were required for simulated anterosuperior (+108.1%; 95% CI, 68.7% to 147.5%, P < .01) and massive (+57.2%; 95% CI, 19.6% to 94.7%, P = .05) cuff tears. Anterior deltoid forces were significantly greater in anterosuperior ( P < .01) and massive ( P = .03) tears. Middle deltoid forces were greater with anterosuperior tears ( P = .03). Posterior deltoid forces were greater with anterosuperior ( P = .02) and posterosuperior ( P = .04) tears. Anterior deltoid force was negatively correlated ( r = −0.89, P = .01) with critical shoulder angle (34.3°; 95% CI, 32.0° to 36.6°). Deltoid forces had no statistical correlation with acromial index (0.55; 95% CI, 0.48 to 0.61). Superior migration was 8.3 mm (95% CI, 5.5 to 11.1 mm) during testing of massive rotator cuff tears. Conclusion: Shoulders with rotator cuff tears require considerable compensatory deltoid function to prevent abduction motion loss. Anterosuperior tears resulted in the largest motion loss despite the greatest increase in deltoid force. Clinical Relevance: Rotator cuff tears place more strain on the deltoid to prevent abduction motion loss. Fatigue or injury to the deltoid may result in a precipitous decline in abduction, regardless of tear size.